Proses Pelaksanaan Gelar Perkara (Studi Urgensi Gelar Perkara Dalam Kelancaran Penyelesaian Perkara Pidana) - Mahalani, Agustina Wahyu; , Muchammad Iksan, SH.MH; , Marisa Kurnianingsih, S.H., M.H., M.Kn (2016)
The purpose of this research is to determine the importance of the process of a case to solve a problems of the criminal case, to find out the process of a case conducted by investigators in uncovering the criminal case and to investigate the problems experienced by the investigator in the execution of a case. The method used in this research is empirical juridical with descriptive research. The data source consists of primary data source, interviews and secondary data source, legal data primary, secondary and tertiary. Data collected from literature study and interviews then analyzed qualitatively. The results showed that a case was implemented to provide legal status for its handling of the case, so that the finishing process does not have any errors in decision-making, which will have an effect in the process of handling criminal cases. The process of a case by the investigator starts from incoming reports, the design of a case, the implementation of a case and the final stage of a case which resulted in a conclusion and it made into the minutes then submitted to the leaders for further action. Factors that obstructing the implementation of a case is many complaints from society and the duration for handling the case is long by law enforcement and a new evidence could impede the course of the criminal case.